Observation of temperature and velocity in the coastal water off Kuala Terengganu, Malaysia - Taira, Keisuke; Saadon, Mohd Nasir; Kitagawa, Shoji; Yanagi, Tetsuo (Kluwer Academic Publishers, 1996)
Mooring observation of current and temperature was made at 17.8 m layer of 19 m depth about 8 km east to Kuala Terengganu, Peninsular Malaysia. Harmonic analysis was applied to tidal currents for 30 days in September 1993, and to the tides observed at Chendering. The K1 tide was the largest both in tidal currents and the tides. Daily mean temperature, currents, sea level, and winds were analyzed from September 1993 to May 1994. Northeast Monsoon from December to February caused sea level rise of 50 cm and temperature lowering of 1°C.